Relationship of Critical Temperature to Macromolecular Synthesis and Growth Yield in Psychrobacter cryopegella - Bakermans, Corien (American Society for Microbiology, 2004)
Most microorganisms isolated from low-temperature environments (below 4°C) are eury-, not steno-, psychrophiles. While psychrophiles maximize or maintain growth yield at low temperatures to compensate for low growth rate, the mechanisms involved remain unknown, as does the strategy used by eurypsychrophiles to survive wide ranges of temperatures that include subzero temperatures. Our studies involve the eurypsychrophilic bacterium Psychrobacter cryopegella, which was isolated from a briny water lens within Siberian permafrost, where the temperature is −12°C. P. cryopegella is capable of reproducing from −10 to 28°C, with its maximum growth rate at 22°C. We examined the temperature dependence of growth rate, growth yield, and macromolecular (DNA, RNA, and protein) synthesis rates for P. cryopegella. Below 22°C, the growth of P. cryopegella was separated into two domains at the critical temperature (T(critical) = 4°C). RNA, protein, and DNA synthesis rates decreased exponentially with decreasing temperatures. Only the temperature dependence of the DNA synthesis rate changed at T(critical). When normalized to growth rate, RNA and protein synthesis reached a minimum at T(critical), while DNA synthesis remained constant over the entire temperature range. Growth yield peaked at about T(critical) and declined rapidly as temperature decreased further. Similar to some stenopsychrophiles, P. cryopegella maximized growth yield at low temperatures and did so by streamlining growth processes at T(critical). Identifying the specific processes which result in T(critical) will be vital to understanding both low-temperature growth and growth over a wide range of temperatures.